Optimal decisions on pricing and greening policies of multiple manufacturers under governmental regulations on greening and carbon emission - De, Manoranjan; Giri, Bibhas Chandra (Decision Making: Applications in Management and Engineering, 2020)
This paper is determines the optimal decisions on pricing and greening strategies of substitutable products which are manufactured by duopoly competitor firms in a consumer sensitive market where a consumer can choose a particular product by its retail price and greening level. The firms simultaneously produce these substitute products under carbon emission regulations enacted by government administration. Government’s carbon emission regulation like carbon tax or cap and trade may not be enough to direct optimization of social greening welfare but may force to mandate the firms to satisfy a standard greening level to handle it. A penalty or subsidy is levied per unit difference in greening standards as well as with the cape and trade regulation on carbon emission. The, contesting firm managers face the problem of fixing the conflicts on carbon penalty and greening investment to decide the optimum policies. For numerical examples, the optimal decisions of the firm managers are obtained by maximizing the profit following government’s mandatory regulations. Some managerial insights are outlined and sensitivity analyses on key parameters of the model are graphically presented.